2014
DOI: 10.1038/ncomms4040
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-free graphene edges

Abstract: Graphene edges and their functionalization influence the electronic and magnetic properties of graphene nanoribbons. Theoretical calculations predict saturating graphene edges with hydrogen lower its energy and form a more stable structure. Despite the importance, experimental investigations of whether graphene edges are always hydrogen-terminated are limited. Here we study graphene edges produced by sputtering in vacuum and direct measurements of the C-C bond lengths at the edge show B86% contraction relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 42 publications
4
77
0
Order By: Relevance
“…3(a,b), the system evolves into a topological superfluids with finite BCS order parameters. The original edge states of the topological insulator are now replaced by the zero energy Majorana boundary states [41] when the chemical potential is in the band gap, similar as previous TI based MF scheme using edge states [36]. More interestingly, when the chemical potential cuts only one of the conduction or valance bands, we find the coexistence of the edge states from the topological insulator and the zero energy Majorana edge states from the topological superconductor.…”
Section: Topological Phase and Majorana Fermions In 1d Latticessupporting
confidence: 63%
See 1 more Smart Citation
“…3(a,b), the system evolves into a topological superfluids with finite BCS order parameters. The original edge states of the topological insulator are now replaced by the zero energy Majorana boundary states [41] when the chemical potential is in the band gap, similar as previous TI based MF scheme using edge states [36]. More interestingly, when the chemical potential cuts only one of the conduction or valance bands, we find the coexistence of the edge states from the topological insulator and the zero energy Majorana edge states from the topological superconductor.…”
Section: Topological Phase and Majorana Fermions In 1d Latticessupporting
confidence: 63%
“…Note that for a 1D non-interacting system with t ⊥ s = 0 and t p = t s , the single particle Hamiltonian H 0 breaks the time reversal symmetry but preserves a chiral symmetry σ y H 0 (k x )σ y = −H 0 (k x ), which realizes an AIII class TI characterized by a Z topological invariant [38,39]. In the topological phase, there are a pair of in-gap topological states on the system boundaries [41][42][43]. When t p = t s , there will be an additional kinetic energy term, which does not change the phase transition and topological properties of the system [44,45].…”
Section: Topological Phase and Majorana Fermions In 1d Latticesmentioning
confidence: 99%
“…The transferred synthetic graphene is found to occasionally have holes, which can be augmented on electron beam irradiation in a low-voltage C s aberration-corrected transmission electron microscope (80 kV acceleration voltage). These freshly in situ-derived edges from the augmented holes provide a clean [previous electron energy loss spectrum and TEM study confirmed no oxygen or nitrogen species on these edges (27) as well as no hydrogen (28)] and convenient platform to study the 1D motion of adsorbed Fe atoms. Because of the larger binding energy of an Fe atom at graphene open edges as opposed to binding at the basal plane, Fe atoms tend to reside at the edges.…”
mentioning
confidence: 85%
“…The presence of interstitial iron atoms is a key ingredient affecting the emergence of bulk superconductivity in Fe1+xTe [2,[6][7][8]18,19]. However, it is worth to notice that superconductivity is also observed up to 13 K in strained thin films of Fe1+xTe, and whose origin is still unclear as its filamentary nature is induced by incorporating oxygen into the bulk phase of Fe1+xTe [20][21][22][23]. The expected coupling/interplay between structural and magnetic degrees of freedom in this material offers a magneto-elastic coupling framework as observed in other iron-based compounds [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The interest is further motivated following the recent observation of an enhanced Tc as high as 50 K, and even reaching 100 K in single layer of un-doped FeSe deposited on SrTiO3 substrate [3,[8][9][10] -offering exceptionally the highest observed Tc for materials other than cuprates. In this context, the parent superconductor iron-tuned telluride, Fe1+xTe, attracted a keen interest and many studies were devoted to probe its microscopic as well as macroscopic properties [6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23]. The nuclear and magnetic structures of Fe1+xTe with different controlled iron excess contents were studied by different authors who determined the underlying characteristics as a function of temperature [11][12][13][14], pressure [15] and magnetic field [16,17].…”
Section: Introductionmentioning
confidence: 99%